A song for the dark times [compact disc, unabridged] : an Inspector Rebus novel - Rankin, Ian (Rankin, Ian. Inspector Rebus novel series., 2020)
When his daughter Samantha calls in the dead of night, John Rebus knows it's not good news. Her husband is missing, and Rebus knows that his daughter will be the prime suspect.